Identifying sex-based disparities in porcine mitochondrial function - Hao Liu; Wenshu Shi; Xing Zhang; Xinmiao He; Xingbo Zhao (Animal Biotechnology)
In pigs, the effect of sex on production and reproductive traits has been largely reported, however, whether sex exerts its influence through regulating mitochondrial function is still unclear. In this study, we constructed 15 male cells and 15 female fibroblasts derived from 35-day and 50-day fetuses, newborn piglets and 1-year-old pigs to identify the sex effect on mitochondrial functions. Results indicated significant differences on cellular and molecular characteristics between male and female cells, including energy metabolic trait, mitochondrial DNA (mtDNA) replication and transcription, and mRNA expressions of mitochondrial biogenesis genes and mitoprotease genes. Referring to sex, males exhibited significantly higher oxygen consumption rate productions, levels of reactive oxygen species (ROS) and mtDNA copy numbers than those with females in muscle and ear fibroblasts. And the expressions of mtDNA, mitochondrial biogenesis genes (POLG, PPARGC1A, TFAM and TWNK) and XPNPEP3 were higher in males than females in ear fibroblasts derived from 1-year-old adult pigs (EFA cells). While, the cell proliferation and expressions of genes related to ROS metabolism were not influenced by sex. The results highlight the effect of sex on mitochondrial function and gene expression, and provide important data for a comprehensive understanding of the mechanisms underlying sex regulation of energy metabolism-related traits in pigs.